Advancing mussel-based monitoring: integrating litter and harmful algal bloom data into a multi-stressor assessment of England and Wales - McGoran, Alexandra R.; Page, Shamina; Lewis, Adam; Bakir, Adil; Barry, Jon; Dean, Karl; Russell, Josie (Frontiers in Marine Science, 2025)
Effective monitoring is essential for decision makers to make informed choices to address pollution issues, including marine litter and microplastics which are subjects of increasing interest. Monitoring biota is essential for estimating the bioavailable fraction of litter in the environment and is a step towards understanding the risks associated with microplastics. The present study assessed the suitability of mussels as a sentinel species in a multi-stressor context. Mussels are already used as sentinel species for many contaminants, including harmful algal blooms, but to date there is no agreed sentinel species targeting microplastics. Mussels from seven locations on the English and Welsh coast were monitored for both microplastics and harmful algal biotoxins. Fluorescent and non-fluorescent microplastics were quantified. Over half (53%) of mussels contained microplastics. No geographical accumulation zones in microplastic abundance were identified at the sample locations with a mean contamination of 1.33 ± 3.04 (SD) items per individual (95% CI = 0.88–1.79) and 0.33 ± 0.71 items per g (wet weight) (95% CI = 0.23–0.44). Five groups of harmful algal toxins were screened within the study animals, with no quantifiable levels of any being present at the time of sampling for this study. However, four of the six sites were exposed to the Diarrhetic shellfish toxins earlier in the year, representing a prior exposure to harmful algal toxins. Research has shown that microplastic exposure alone does not always negatively impact organisms. But there is mounting evidence that microplastics may increase sensitivity and susceptibility to other stressors in the environment. Given the presence of both microplastics and algal neurotoxins in oceans around the world and the concern for multi-stressor impacts on the marine environment, it is proposed that multi-factor monitoring could provide insight into the true risk of microplastics as a contaminant vector and antagonistic pollutant. This evidence is urgently needed to support governments globally in creating mitigation strategies and monitoring the success of these interventions. The present study finds that mussels are a suitable sentinel species for this use, but ongoing research is needed to determine special and temporal variations.